Pelatihan komunikasi efektif berbasis media sosial bersama ppni komisariat rsud karawang - Nursanti, Siti; Dharta, Firdaus Yuni; Chaerudin, Chaerudin; Syam, Syisea Putri; Purnama, Rifki Nugraha (Fakultas Ilmu Komunikasi Universitas dr. Soetomo, 2021)
The abundance of information related to the Covid-19 virus has created a crisis of public confidence in the massively spreading information related to handling of the pandemic. Professionals in the field of communication and health must produce reliable health information. Therefore, it is necessary to conduct training for health workers on carrying out health literacy to patients and the community using social media. With the expertise possessed by the servant in collaboration with the Indonesian National Nurses Association, the Karawang Hospital Commissariat became a facilitator in Social Media-Based Effective Communication Training at Karawang Hospital. This event was conducted online using the zoom.us application, followed by health workers in the Karawang Regional Hospital. This event is expected to improve the skills of health workers to produce health information and disseminate it to the broader community so that the Covid-19 virus problem can be resolved immediately.